A Report on nitrocellulose manufacture - Espejo, Manuel A. (College of Engineering, 1963)
That the commercial production of nitrocellulose from bagasse for the plastics industry is feasible is stating too weakly the possibilities of such a venture. This design project points out that with a capital of P13.5 million, a nitrocellulose plant of 12,00 lbs. per day capacity could be expected to break-even at 36.5 percent of the production level, that pay-out time could be estimated as 4.12 years and that the percent return on investment woule be .1435. It may be very well said that the establishment of such a plant at the earliest possible time to take advantage of the absence of competition, would be most advisable.